Can heat-pressed feldspathic ceramic be submitted to multiple heat-pressing? - Dal Piva, Amanda Maria de Oliveira [UNESP]; Barcellos, Aline Serrado de Pinho [UNESP]; Bottino, Marco Antonio [UNESP]; Souza, Rodrigo Othávio de Assunção E; Melo, Renata Marques de [UNESP] (FapUNIFESP (SciELO), 2018)
The aim of this study was to determine if multiple processing (heat-pressing) of a dental ceramic influences flexural strength, hardness, and microstructure. Ninety bar-shaped specimens (15 mm × 4 mm × 2 mm) of a pressed ceramic (Vita PM9) were fabricated and randomly divided into 6 groups (n = 15) according to the factors number of pressings (C1, C2, and C3, fired 1, 2, and 3 times, respectively) and mechanical cycling (M). Half of the specimens were mechanically cycled (106 cycles, 45 N, 3.4 Hz, in water) and all specimens were tested for 3-point bending (0.5 mm/min, load 1000 kgf) and Vickers hardness (19.6 N for 20 s). X-ray diffraction was used to characterize the phases and scanning electron microscopy to characterize the microstructure. The flexural strength data was statistically analyzed with Weibull analysis, ANOVA, and Tukey test. Hardness data was evaluated by 2-way ANOVA and Fisher test. All tests were performed with a significance level of 0.05. Two-way ANOVA revealed that neither number of pressings (p=0.085) or mechanical cycling (0.055) significantly affected flexural strength. But Weibull analysis showed significant difference for Weibull moduli and characteristic strength between groups. For hardness, a statistical difference was seen for the interaction Number of pressings * Mechanical cycling, (p = 0.016). Hardness decreased in the following order: C1 (775±17.2), CM3 (751±101), CM2 (735±45), C3 (701±82), CM1 (671±82), and C2 (663±92). Fewer defects were observed with an increased number of firings. Therefore, the possibility of recycling PM9 ceramic does not interfere in the evaluated mechanical properties and improves microstructure.